Herbaspirillum Infection in Humans: A Case Report and Review of Literature - Rashmi Dhital; Anish Paudel; Nidrit Bohra; Ann K. Shin (Case Reports in Infectious Diseases)
Introduction. Herbaspirillum seropedicae are Gram-negative oxidase-positive nonfermenting rods of Betaproteobacteria class, commonly found in rhizosphere. More recently, some Herbaspirillium species have transitioned from environment to human hosts, mostly as opportunistic (pathogenic) bacteria. We present a 58-year-old female with non-small-cell lung cancer (NSCLC) who presented with pneumonia and was found to have Herbaspirillum seropedicae bacteremia. Case History. A 58-year-old woman with NSCLC on Pralsetinib presented with fevers and rigors for 2 days. Coarse breath sounds were auscultated on the right upper lung field. Labs revealed leukopenia and mild neutropenia. CT chest revealed right upper lobe pneumonia. She was admitted for sepsis secondary to pneumonia and placed on broad spectrum antibiotics with intravenous piperacillin-tazobactam and vancomycin. The patient continued to have fever 2 days after admission (max: 102.8°F). Preliminary blood cultures grew Gram-negative rods. The patient continued to have temperature spikes on the 3rd day of antibiotics (Tmax 101.5°F). Blood cultures revealed oxidase-positive nonfermenting rods. The patient’s antibiotic was changed to IV meropenem on the 4th day of hospitalization. Ultimately, on the seventh day of hospitalization, the blood culture was confirmed from outside lab as Herbaspirillum seropedicae. The patient started feeling better and defervesced after about 24 hours. Discussion. More recently, Herbaspirillum spp. have been recovered from humans. Our patient had Herbaspirillum bacteremia, and reported regularly cleaning her pond and weeding her garden with possible exposure to this environmental proteobacterium. Herbaspirillum may be more prevalent than earlier thought owing to misidentification. With the institution of appropriate antimicrobial therapy, the outcomes seem mostly favorable.